Pengujian LCC Mucuna bracteata di Berbagai Kemiringan Lahan Terhadap Perkembangan Mesofauna Tanah dan Akar Kelapa Sawit TBM - III - Khaidir, Muhammad; Wawan, Wawan; Idwar, Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the effect of LCC Mucuna bracteata in various slope on the development of soil mesofauna and growth of oil palm TBM - III. This research has been conducted in PTPN V Unit Lubuk Dalam, Siak and analysis mesofauna soil in Soil Laboratory, Faculty of Agriculture, University of Riau. The study lasted from January to April 2016. The study was conducted by using split plot design. The level of slope (K) as the main plot, which are: K1 = land slope of 0% - 3%, K2 = land slope >3% - 8%, K3 = land slope >8% - 15%. Testing LCC Mucuna bracteata (M) as the subplot, which are: M0 = land planted with oil palm without LCC Mucuna bracteata, M1 = land planted with oil palm LCC Mucuna bracteata. The parameters measured were the number of family, total individual, population density (K), relative density (KR), diversity index (H ') of soil mesofauna, root dry weight, root volume and root occupy. The results showed: (1) land planted with oil palm with LCC Mucuna bracteata has a number of families, total individuals and diversity soil mesofauna higher in than those without LCC Mucuna bracteata both at the level of land slope 0% - 3% >3% - 8% , and >8% - 15%; (2) The higher the slope (%), the total individual and population density (K) soil mesofauna lower; and (3) root dry weight, root volume and root occupy a tendency to increase the area planted with Mucuna bracteata LCC compared to land without LCC Mucuna bracteata. Keywords: Mucuna bracteata, land slope and mesofauna